Exploring the causal association between genetically determined circulating metabolome and hemorrhagic stroke - Wang, Yaolou; Shen, Yingjie; Li, Qi; Xu, Hangjia; Gao, Aili; Li, Kuo; Rong, Yiwei; Gao, Shang; Liang, Hongsheng; Zhang, Xiangtong (Frontiers in Nutrition, 2024)
Hemorrhagic stroke (HS), a leading cause of death and disability worldwide, has not been clarified in terms of the underlying biomolecular mechanisms of its development. Circulating metabolites have been closely associated with HS in recent years. Therefore, we explored the causal association between circulating metabolomes and HS using Mendelian randomization (MR) analysis and identified the molecular mechanisms of effects.We assessed the causal relationship between circulating serum metabolites (CSMs) and HS using a bidirectional two-sample MR method supplemented with five ways: weighted median, MR Egger, simple mode, weighted mode, and MR-PRESSO. The Cochran Q-test, MR-Egger intercept test, and MR-PRESSO served for the sensitivity analyses. The Steiger test and reverse MR were used to estimate reverse causality. Metabolic pathway analyses were performed using MetaboAnalyst 5.0, and genetic effects were assessed by linkage disequilibrium score regression. Significant metabolites were further synthesized using meta-analysis, and we used multivariate MR to correct for common confounders.We finally recognized four metabolites, biliverdin (OR 0.62, 95% CI 0.40-0.96, PMVMR= 0.030), linoleate (18. 2n6) (OR 0.20, 95% CI 0.08-0.54, PMVMR =0.001),1eicosadienoylglycerophosphocholine* (OR 2.21, 95% CI 1.02-4.76, PMVMR =0.044),7-alphahydroxy-3 -oxo-4-cholestenoate (7-Hoca) (OR 0.27, 95% CI 0.09-0.77, PMVMR =0.015) with significant causal relation to HS.We demonstrated significant causal associations between circulating serum metabolites and hemorrhagic stroke. Monitoring, diagnosis, and treatment of hemorrhagic stroke by serum metabolites might be a valuable approach.